Badania nad Własnościami Reologicznych Układów Rozproszonych - Wołarowicz, M.P. (Engineering Transactions, 1955)
A definition of rheology is given and the scope of this branch of science is discussed as well as different kinds of dispersed systems, that is, easily deformable materials, which undergo rheological investigations in various industries. This is followed by a short account of the history of the development of rheology in Russia prior to the revolution, which is linked with such famous names as M. V. Lomonosow, D. J. Mendeleiev, N. P. Petrov, F. N. Shvedov, N. S. Kurnakow and others. Next, the work of Soviet scientists associated with investigations of rheological properties of dispersed systems, is discussed. The examples used were taken mainly from the works of the author and his co-workers. The phenomenological theory of viscoplastic flow of dispersed systems, based on the equations of Shvedov-Hencky-Iliushin, is presented. The equations in question are discussed in a series of problems and include the following: flow through a circular or annular tube as well as through a flat capillary tube; rotational motion in a narrow space formed by two coaxial cylindrical surfaces; rotation of a shaft in a bearing; longitudinal displacement of a cylinder; gravity flow down a slope, etc. The methods of investigation are described, including integration methods and instruments (rotation and capillary viscometers, slide plate instruments, etc.), as well as differentiation methods, methods permitting the study of the deformation and the rate of deformation considered at any point of the dispersed mass. The advantages of instruments, in which the dispersed system remains during the test, in a state of homogeneous shear, are discussed. Some results of measurements of rheological properties of dispersed systems (plastic viscosity, limit, shear stress, etc.) are presented and the molecular colloidal interpretation of viscoplastic flow of dispersed masses in discussed. Finally, the paper brings some examples of practical application of the results obtained by rheological investigation.